Discipline, Motivation, Local Wisdom, And Work Environment On Performance Through Job Satisfaction - Fatmasari Fatmasari; Badaruddin Badaruddin (Jurnal Manajemen, 2022)
This study is intended to examine the effect of discipline, motivation, local wisdom, and work environment on employee performance through job satisfaction as an intervening. This research is in the form of an explanation pattern approach that uses primary data and secondary data collected using interviews, observation, questionnaires, and documentation. The population in this study was echelon Officials in the Regional Apparatus Organizations (OPD) within the Parepare City Government, consisting of echelon II, III, and IV officials with a total of 532 people. The research sample amounted to 84 people generated through the Slovin formulation. Data analysis was performed using descriptive and inferential statistical analysis (applying Structural Equation Modeling (SEM) using the Smart PLS Version 3.0 program). The results showed that discipline, motivation, local wisdom, and work environment had a positive and significant direct influence on job satisfaction. Discipline, motivation, local wisdom, and work environment positively and significantly affect employee performance. The impact of job satisfaction as an intervening variable cannot strengthen the relationship between discipline and employee performance. The impact of job satisfaction as an intervening variable can enhance the relationship between motivation, local wisdom, and work environment on employee performance. Job satisfaction has a positive and significant effect on employee performance.